THE HIDDEN MEANING OF MANIPULATIVE LANGUAGE IN LOVE BOMBING: A STUDY OF ILLOCUTIONARY ACTS IN NARCISSISTIC RELATIONSHIPS - Rachmawati Setyaningsih; Rakhmawati, Fitri (Lire Journal (Journal of Linguistics and Literature), 2025)
Love bombing is a dangerous phenomenon in relationships, where a narcissistic perpetrator uses language to manipulate their victim. This study aims to uncover the hidden meanings behind Jake’s love bombing language, revealing the manipulative intent behind his words. A qualitative descriptive approach is employed to analyze the language of love bombing within a narcissistic relationship. The data consists of 50 utterances from the short movie Love Bomb, spoken by Jake, the narcissistic character, towards Skye as his victim. Data were collected through observation, selecting utterances with significant manipulative intent from the official YouTube channel @integratebristol. In the analysis, Jake’s utterances are categorized into two stages of narcissistic abuse based on Grossi: idealization (18 utterances) and devaluation (32 utterances). In the idealization stage, he uses flattering language to create an illusion of love and emotional connection with Skye. As the relationship shifts to devaluation, his language becomes manipulative, controlling, and aggressive, aimed at diminishing Skye’s self-esteem and asserting dominance. Using Searle’s taxonomy of illocutionary acts, Jake’s utterances are classified into assertives, directives, commissives, expressives, and declarations. The findings show that during the idealization stage, Jake’s utterances consist of assertives (38.89%), directives (16.67%), commissives (0%), expressives (44.44%), and declarations (0%). In the devaluation stage, the distribution shifts to assertives (31.25%), directives (43.75%), commissives (18.75%), expressives (6.25%), and declarations (0%). Further analysis using Austin’s speech act theory reveals that Jake’s locutionary acts often differ from his literal meaning, while his perlocutionary effects shape Skye’s emotions and decisions. The study concludes that love bombing conceals strategic manipulation through exaggerated praise, conditional affection, and guilt-inducing phrases. This demonstrates how manipulative language in love bombing enables the perpetrator to maintain power and control in relationships